Routledge Handbook of Gender and Agriculture (Taylor & Francis, 2020)
The Routledge Handbook of Gender and Agriculture covers major theoretical issues as well as critical empirical shifts in gender and agriculture. Gender relations in agriculture are shifting in most regions of the world with changes in the structure of agriculture, the organization of production, international restructuring of value chains, climate change, the global pandemic, and national and multinational policy changes. This book provides a cutting-edge assessment of the field of gender and agriculture, with contributions from both leading scholars and up-and-coming academics as well as policymakers and practitioners. The handbook is organized into four parts: part 1, institutions, markets, and policies; part 2, land, labor, and agrarian transformations; part 3, knowledge, methods, and access to information; and part 4, farming people and identities. The last chapter is an epilogue from many of the contributors focusing on gender, agriculture, and shifting food systems during the coronavirus pandemic. The chapters address both historical subjects as well as ground-breaking work on gender and agriculture, which will help to chart the future of the field. The handbook has an international focus with contributions examining issues at both the global and local levels with contributors from across the world. With contributions from leading academics, policymakers, and practitioners, and with a global outlook, the Routledge Handbook of Gender and Agriculture is an essential reference volume for scholars, students, and practitioners interested in gender and agriculture.
English
Keywords: Applied ecology; Environmental policy and protocols; Gender studies, gender groups; Nature and the natural world: general interest; Nature, Ecology, Agriculture, Gender and Development